JNK1 Signaling Downstream of the EGFR Pathway Contributes to Aldara®-Induced Skin Inflammation - Le, Aurore; Azouz, Abdulkader; Thomas, Séverine; Istaces, Nicolas; Nguyen, Muriel; Goriely, Stanislas (Frontiers in Immunology, 2021)
c-Jun N-terminal protein kinase 1 (JNK1) is involved in multiple biological processes but its implication in inflammatory skin diseases is still poorly defined. Herein, we studied the role of JNK1 in the context of Aldara-induced skin inflammation. We observed that constitutive ablation of JNK1 reduced Aldara-induced acanthosis and expression of inflammatory markers. Conditional deletion of JNK1 in myeloid cells led to reduced skin inflammation, a finding that was associated with impaired Aldara®-induced inflammasome activation in vitro. Next, we evaluated the specific role of JNK1 in epidermal cells. We observed reduced Aldara-induced acanthosis despite similar levels of inflammatory markers. Transcriptomic and epigenomic analysis of keratinocytes revealed the potential involvement of JNK1 in the EGFR signaling pathway. Finally, we show that inhibition of the EGFR pathway reduced Aldara-induced acanthosis. Taken together, these data indicate that JNK1 plays a dual role in the context of psoriasis by regulating the production of inflammatory cytokines by myeloid cells and the sensitivity of keratinocytes to EGFR ligands. These results suggest that JNK1 could represent a valuable therapeutic target in the context of psoriasis.